Dance as a means to accompany the migratory challenge faced by students about to graduate from the I.E.D. Republic of Korea of ​​La Peña, Cundinamarca. (The Voz a Vos Bulletin, 2025)
My research proposes the articulation of dance with a social issue such as youth migration in rural contexts. The dance is not only as a repetitive act, but as a pedagogical and transformative tool capable of generating bonds, strengthening identities, and emotionally supporting young people who face migratory processes.The objective is to understand how dance practice can serve as a means of sensitive and emotional accompaniment, allowing students to narrate and re-signify their migratory experiences, build collective memory, and find spaces for the expression of their cultural identity. This approach seeks to go beyond mere spectacle, positioning dance as a resource for emotional and social containment.“At the methodological level, the research adopts a qualitative approach based on Participatory Action Research. This methodological choice seeks to ensure that students are not merely subjects of study, but rather protagonists in the creation of knowledge. Several possible data collection strategies are considered, such as dance workshops, interviews, field journals, and participatory observation, which could enable the collective construction of experiences and knowledge.”The participants are students about to graduate from the I.E.D. República de Corea, especially those who have migration in their life plans or are already in the process of migrating. The participation of different actors from the educational community is also contemplated, with the purpose of enriching the analysis, planning the accompaniment, and monitoring the implementation of the proposal.This research arises from the need to respond to a social issue identified in La Peña, particularly at the I.E.D. República de Corea: the emotional, sentimental, and cultural challenges students face in the context of migration, often without adequate institutional or family support. Furthermore, its scope is directed not only at migrant students and their families, but also at educational institutions and organizations that seek to promote emotional well-being and youth social cohesion.
Keywords: Migration; Dance; Emotions